Generation of a continuous-wave squeezed vacuum state at 1.3 μm by employing a home-made all-solid-state laser as pump source - 郑耀辉 邬志强 霍美茹 周海军 (Chinese physics B, 2013)
We present a continuous-wave squeezed vacuum generation system at a telecommunication wavelength of 1.3 μm. By employing a home-made single-frequency Nd：YVO4 laser with dual wavelength outputs as the pump source, via an optical parameter oscillator based on periodically poled KTR a squeezed vacuum of 6.1 dB＋0.1 dB below the shot noise limit at 1342 nm is experimentally measured. This system could be utilized for demonstrating practical quantum information networks.